Body composition and lipid profiles, quality of life, self-concept, and nutritional knowledge of Pahlavani wrestlers in Kermanshah - Alireza Jamshidi; Rastegar Hoseini; Hossein Pirani; Ehsan Amiri (Sport Sciences and Health Research)
Background: Pahlavani wrestling is one of the ancient sports in Iran. However, very few studies have been conducted on various aspects of it.Aim: To investigate the body composition, lipid profile, quality of life, self-concept, and nutritional knowledge of Pahlavani wrestlers of Kermanshah city.Materials and Methods: Fifty-seven adult Pahlavani wrestlers participated in this study. They completed the quality of life, self-concept, and nutritional knowledge questionnaires on three consecutive days, and then, on two separate days, their body composition and lipid profile were also measured.Results: The quality of life, muscle mass percentage, and bone and mineral content were significantly higher than the normal values (P˂0.05). Also, the lipid profile was in a normal state. Conversely, the self-concept, nutritional knowledge, nutritional attitude, and nutritional practice were significantly lower than the normal values of these variables (P˂0.05). Finally, the BMI was significantly lower than the normal value (P˂0.05) and the fat percentage and visceral fat index were not significantly different (P˃0.05) from their normal values.Conclusion: The results indicated that Pahlavani wrestlers of Kermanshah are in favorable conditions in many physical and body composition health indicators, which somehow shows the possible positive effects of this sport on different aspects of health. However, Pahlavani wrestlers had a considerably lower self-concept and nutritional knowledge than the normal values.